2014
DOI: 10.1177/1470593114553329
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking religion in the context of ethnicity and well-being

Abstract: Identifying the 'religion-ethnicity-wellbeing' nexus as an understudied topic in marketing and consumer behavior research, we propose three main trajectories for future research: Firstly, given the politics of religions, there is a need for studying societies that suffer from and are affected by religio-ethnic tensions and also different types of risks that threaten people's wellbeing in such contexts. Secondly, future research should investigate how and why markets may generate and mediate religio-ethnic prej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…Yet, what we want to highlight here is that one cannot simply assume that a common understanding of religion's objectives (Magasid Ash Shari'ah) exists among Moslems. The world we are living in today is becoming increasingly and sadly prone to religion-related violence and conflicts most of which happen in everyday life situations such as markets, servicescapes and consumptionscapes (Jafari, 2015;Jafari, Özhan Dedeoğlu, Üstündağli, Regany & Batat, 2015). A closer analysis of such discrepancies can reveal that what causes conflict is not religion per se but the ways people choose to interpret religions and religiosity.…”
Section: Ideological Readings Of Islammentioning
confidence: 99%
“…Yet, what we want to highlight here is that one cannot simply assume that a common understanding of religion's objectives (Magasid Ash Shari'ah) exists among Moslems. The world we are living in today is becoming increasingly and sadly prone to religion-related violence and conflicts most of which happen in everyday life situations such as markets, servicescapes and consumptionscapes (Jafari, 2015;Jafari, Özhan Dedeoğlu, Üstündağli, Regany & Batat, 2015). A closer analysis of such discrepancies can reveal that what causes conflict is not religion per se but the ways people choose to interpret religions and religiosity.…”
Section: Ideological Readings Of Islammentioning
confidence: 99%
“…The observation of the media diet of the sample consulted clearly reflects the domination of two media sources of information and entertainment: Internet (mentioned by 19 of the interviewed) and television (17). All Internet users indicated that they regularly use Youtube and Facebook.…”
Section: Preferred Mediamentioning
confidence: 94%
“…The participation of religion in those processes of cultural hybridization that evolve unavoidably after a migratory experience has been addressed by multiple authors, such as Jafari, Özhan, Regany, Úrstündagli and Batat [17], Göle [15], Abu-Lughod [18] or Zanfrini [19]. But, perhaps logically, no univocal answer has been reached beyond the recognition of how difficult it is to study.…”
Section: The Media Consumption Of the Muslim Migrant Populationmentioning
confidence: 99%
“…Here the very limited evidence is less optimistic. When religious pluralism and secularism increase, the advantages associated with religious identity are likely to diminish as modernization and religious hybridization affect traditional consumption norms (Jafari and Suerdem 2012; Jafari et al 2015). Further, we observe both hospitals and colleges with historical religious identities in the US and Canada abandoning the governance structures that reinforced them and, in some cases, their religious identity itself.…”
Section: Further Inquiry: Macromarketing Research Opportunitiesmentioning
confidence: 99%